1999
DOI: 10.1046/j.1442-200x.1999.4121032.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death in school children: Role of physical activities and meteorological conditions

Abstract: Sudden deaths in children at school may be associated with physical activities and meteorological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Previous reports have shown that sudden death in childhood and adolescence has been rare. [11][12][13][14][15] Population-based reports show the rate of sudden death ranged from 1.3 to 8.5 per 100,000 patientyears.l4 Our patient was a healthy young girl recovered from cardiopulmonary arrest. She had provoked coronary artery spasms with the administration of ACh and had myocardial ischemia demonstrated by ECG, echocardiogram, and 123I-MIBG myocardial scintigraphic imaging.…”
Section: Discussionmentioning
confidence: 91%
“…Previous reports have shown that sudden death in childhood and adolescence has been rare. [11][12][13][14][15] Population-based reports show the rate of sudden death ranged from 1.3 to 8.5 per 100,000 patientyears.l4 Our patient was a healthy young girl recovered from cardiopulmonary arrest. She had provoked coronary artery spasms with the administration of ACh and had myocardial ischemia demonstrated by ECG, echocardiogram, and 123I-MIBG myocardial scintigraphic imaging.…”
Section: Discussionmentioning
confidence: 91%
“…We confirmed the previous result 4 that relative humidity and wind did not influence the rate of sudden death, however, another study 37 reported an increased hospital admission at the time of increased wind and low humidity. Takada et al 21 found a positive relationship between sudden death during competitive sports and dry and cloudy weather conditions. Shkolnikov et al 38 estimated the medium and greater levels of intoxication occurred in a quarter of those recorded as dying from cardiovascular disease, and they stated that among young men, whose deaths were ascribed to cardiovascular disease, were in reality simply by alcohol poisoning.…”
Section: Discussionmentioning
confidence: 98%
“…A Japanese study reported on 76 victims of school-associated sudden death in whom obvious causative diseases were not detected prior to death. 12 Deaths were associated with vigorous activities, particularly running, and influenced by meteorological conditions. For example, dryness and high pressure in spring were related to deaths in children running.…”
Section: Introductionmentioning
confidence: 99%